Polysaccharides with immunomodulating activity from roots of Gentiana crassicaulis. (15th September 2017) - Zou, Yuan-Feng; Fu, Yu-Ping; Chen, Xing-Fu; Austarheim, Ingvild; Inngjerdingen, Kari Tvete; Huang, Chao; Lei, Fei-Yi; Song, Xu; Li, Lixia; Ye, Gang; Eticha, Lemlem Dugassa; Yin, Zhongqiong; et al.
Highlights: Two polysaccharide fractions were purified from roots of Gentiana crassicaulis . These two fractions were pectic polysaccharides. These two polysaccharides could be used as a potential natural immunomodulator. Abstract: Two polysaccharides, GCP-I-I and GCP-II-I, were obtained from 100 °C water extracts of Gentiana crassicaulis roots by DEAE anion exchange chromatography and gel filtration. The results from methanolysis, methylation, FT-IR and NMR, indicated that these two fractions are typical pectic polysaccharides, with HG and RG-I regions and AG-I/AG-II side chains, and some of the galacturonic acid units of fraction GCP-I-I were methyl esterified. Fractions GCP-I-I and GCP-II-I, both exhibited potent complement fixation, and fraction GCP-I-I was more potent than positive control BPII. The higher complement fixation activity obtained in fraction GCP-I-I may be due to the higher Mw and/or higher amount of AG-II present in fraction GCP-I-I than fraction GCP-II-I. The polysaccharides from G. crassicaulis could be used as a potential natural immunomodulator.